2017
DOI: 10.4103/ejd.ejd_352_16
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of two interactive educational methods to teach tobacco cessation counseling for senior dental students

Abstract: Objective:Nowadays, one of the major health problems in many countries is tobacco use. Dental professionals are in a unique position to promote smoking cessation since they have the opportunity for regular interaction with their patients. The purpose of the present study was to compare the effectiveness of two educational methods to teach tobacco cessation counseling (TCC) in dental practice for senior dental students.Materials and Methods:In this interventional study, 93 eligible senior dental students from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 18 publications
(36 reference statements)
0
5
0
1
Order By: Relevance
“…Several teaching interventions on tobacco‐related diseases and counselling approaches for medical students and, more recently, also for dental students have been described . However, the majority of these studies cannot be compared with the data presented here as most of them were implemented in the United States or other non‐EU countries whose healthcare systems are considerably different from the situation in Germany, where cessation medication is not covered by health insurance and there is no national network of stop smoking services.…”
Section: Discussionmentioning
confidence: 98%
“…Several teaching interventions on tobacco‐related diseases and counselling approaches for medical students and, more recently, also for dental students have been described . However, the majority of these studies cannot be compared with the data presented here as most of them were implemented in the United States or other non‐EU countries whose healthcare systems are considerably different from the situation in Germany, where cessation medication is not covered by health insurance and there is no national network of stop smoking services.…”
Section: Discussionmentioning
confidence: 98%
“…Nevertheless, it has a significant impact upon the processes of learning, especially when combined with physical practice. 6,7 This impact has been observed at both neurological and behavioral levels. 8 It is suggested that processing mechanisms associated with physical movement and observation are mediated via similar processes.…”
Section: Introductionmentioning
confidence: 99%
“…Active learning approaches such as problem-based learning, case studies and practical training have been shown to be more successful than the traditional model, providing a dynamic and engaging experience for dental students. [15][16][17][18] Practical training would ideally use human teeth to mimic clinical work. 19 However, human-extracted teeth with real cases of secondary caries progression are difficult to obtain, and thus, other alternatives must be used in the teaching process.…”
Section: Introductionmentioning
confidence: 99%
“…Practical training in detection and management of secondary caries could be an alternative tool for improving dentist and undergraduate student competencies. Active learning approaches such as problem‐based learning, case studies and practical training have been shown to be more successful than the traditional model, providing a dynamic and engaging experience for dental students …”
Section: Introductionmentioning
confidence: 99%